Anticancer Effect of Nemopilema nomurai Jellyfish Venom on HepG2 Cells and a Tumor Xenograft Animal Model. (13th July 2017) - Lee, Hyunkyoung; Bae, Seong Kyeong; Kim, Munki; Pyo, Min Jung; Kim, Minkyung; Yang, Sujeoung; Won, Chung-kil; Yoon, Won Duk; Han, Chang Hoon; Kang, Changkeun; Kim, Euikyung
Abstract : Various kinds of animal venoms and their components have been widely studied for potential therapeutic applications. This study evaluated whether Nemopilema nomurai jellyfish venom (NnV) has anticancer activity. NnV strongly induced cytotoxicity of HepG2 cells through apoptotic cell death, as demonstrated by alterations of chromatic morphology, activation of procaspase-3, and an increase in the Bax/Bcl-2 ratio. Furthermore, NnV inhibited the phosphorylation of PI3K, PDK1, Akt, mTOR, p70S6K, and 4EBP1, whereas it enhanced the expression of p-PTEN. Interestingly, NnV also inactivated the negative feedback loops associated with Akt activation, as demonstrated by downregulation of Akt at Ser473 and mTOR at Ser2481. The anticancer effect of NnV was significant in a HepG2 xenograft mouse model, with no obvious toxicity. HepG2 cell death by NnV was inhibited by tetracycline, metalloprotease inhibitor, suggesting that metalloprotease component in NnV is closely related to the anticancer effects. This study demonstrates, for the first time, that NnV exerts highly selective cytotoxicity in HepG2 cells via dual inhibition of the Akt and mTOR signaling pathways, but not in normal cells.